Temporal bone marrow of the rat and its connections to the inner ear - Perin, Paola; Cossellu, Daniele; Vivado, Elisa; Batti, Laura; Gantar, Ivana; Voigt, Fabian F.; Pizzala, Roberto (Frontiers in Neurology, 2024)
Calvarial bone marrow has been found to be central in the brain immune response, being connected to the dura through channels which allow leukocyte trafficking. Temporal bone marrow is thought to play important roles in relation to the inner ear, but is still largely uncharacterized, given this bone complex anatomy. We characterized the geometry and connectivity of rat temporal bone marrow using lightsheet imaging of cleared samples and microCT. Bone marrow was identified in cleared tissue by cellular content (and in particular by the presence of megakaryocytes); since air-filled cavities are absent in rodents, marrow clusters could be recognized in microCT scans by their geometry. In cleared petrosal bone, autofluorescence allowed delineation of the otic capsule layers. Within the endochondral layer, bone marrow was observed in association to the cochlear base and vestibule, and to the cochlear apex. Cochlear apex endochondral marrow (CAEM) was a separated cluster from the remaining endochondral marrow, which was therefore defined as “vestibular endochondral marrow” (VEM). A much larger marrow island (petrosal non-endochondral marrow, PNEM) extended outside the otic capsule surrounding semicircular canal arms. PNEM was mainly connected to the dura, through bone channels similar to those of calvarial bone, and only a few channels were directed toward the canal periosteum. On the contrary, endochondral bone marrow was well connected to the labyrinth through vascular loops (directed to the spiral ligament for CAEM and to the bony labyrinth periosteum for VEM), and to dural sinuses. In addition, CAEM was also connected to the tensor tympani fossa of the middle ear and VEM to the endolymphatic sac. Endochondral marrow was made up of small lobules connected to each other and to other structures by channels lined by elongated macrophages, whereas PNEM displayed larger lobules connected by channels with a sparse macrophage population. Our data suggest that the rat inner ear is surrounded by bone marrow at the junctions with middle ear and brain, most likely with “customs” role, restricting pathogen spread; a second marrow network with different structural features is found within the endochondral bone layer of the otic capsule and may play different functional roles.